Student’s mathematical connection reviewed from learning motivation in Advance Organizer Learning assisted by Schoology - Pratama, Rizky Sandy; Mulyono, Mulyono (Department of Mathematics, Universitas Negeri Semarang, 2020)
Abstract The research aims to determine if advanced Organizer learning is effective with the ability of the student’s mathematical connection and describing the mathematical connection ability of students reviewed from the motivation to learn at Advanced Organizer Learning Assisted schoology. The research method used is mixed method with sequential explanatory design. The research population is class IX Junior High School 33 Semarang, while the sample is IX C class as the research class. Samples were taken using the random sampling cluster technique. Subjects of the study were taken using purposive sampling techniques, so obtained six research subjects were selected based on the category of motivational learning. Methods of collecting data using observations, tests, polls, and interviews. The results showed that (1) the proportion of the students ' mathematical connection ability to the study of Schoology advanced Organizer is achieving the classical, average mathematical connection ability of students in Advance Organizer learning With the help of schoology reaching the Minimum Submission Criteria (MSC), and the mathematical connection ability of students after receiving Advance Organizer learningassisted schoology increased by 0.8. The results showed that Advance Organizer learning assisted schoology effectively on the ability of student mathematical connection. (2) Subjects with high learning motivation tend to meet all mathematical connection indicators. Subjects with motivational learning are likely to meet two of the three mathematical connection indicators. Subjects with low learning motivation tend to meet one of three mathematical connection indicators.